Fiberoptic bronchoscopy for the prevention of ventilator-associated pneumonia: a meta-analysis of randomized controlled trials - Tang, Haowei; Yuan, Zhi; Li, Jingjie; Wang, Qun; Fan, Weijie (The Journal of Infection in Developing Countries, 2024)
Introduction: Ventilator-associated pneumonia (VAP) causes increased time of mechanical ventilation (MV), prolonged intensive care unit (ICU) stay, and a higher mortality risk. The systematic review and meta-analysis aimed to compare the efficacies between fiberoptic bronchoscopy (FOB) and general sputum suction for the prevention of VAP in patients with invasive MV. Methodology: Relevant randomized controlled trials (RCTs) were obtained via a search of PubMed, Embase, Cochrane Library, Wanfang, and CNKI databases. A random-effects model was used to pool the results if significant heterogeneity was observed. Otherwise, a fixed-effects model was used. Results: Sixteen RCTs were included. Compared to general sputum suction, sputum suction with FOB was associated with a significantly reduced risk of VAP (risk ratio [RR]: 0.56, 95% CI: 0.47 to 0.67, p < 0.001; I2 = 0%). Subgroup analyses showed that the combination of FOB-assisted sputum suction with bronchoalveolar lavage (BAL) further reduced the risk of VAP as compared to FOB-assisted sputum suction alone (p for subgroup difference = 0.04). In addition, FOB-assisted treatment was also associated with a reduced MV time (mean difference [MD]: -2.19 days, 95% CI: -2.69 to -1.68, p < 0.001; I2 = 18%), a shorter ICU stay (MD: 2.9 days, 95% CI: -3.68 to -2.13, p < 0.001; I2 = 34%), and a reduced mortality risk (RR: 0.46, 95% CI: 0.24 to 0.90, p = 0.02; I2 = 0%) in patients with invasive MV. Conclusions: FOB for sputum suction and BAL in patients with invasive MV is effective in reducing the incidence of VAP.